VLADIMIR SOLOVIEV'S WAY TO “THE HISTORY AND THE FUTURE OF THEOCRACY”: CONTROVERSY ABOUT THE DOGMATIC DEVELOPMENT OF THE CHURCH ON THE PAGES OF “FAITH AND REASON” MAGAZINE (1884-1891) - A. V. Chernyaev; A. Yu. Berdnikova (RUDN Journal of Philosophy, 2019)
The main article is devoted to the historical and philosophical reconstruction of controversy between Vladimir Solovyov and the authors of the “Faith and Reason” - a magazine of the Kharkov Theological Seminary. This controversy took its place in the “theological and journalistic” or the “theocratic” period of Solovyov’s works (1880s). Particular attention is paid to the disputes of Solovyov and T. Stoyanov (Konstantin Istomin), A.P. Shost'in and the French Orthodox priest Fr. Vladimir Gette on the theory of dogmatic development in the church. In the context of this controversy, the arguments for the “defense” of Solovyov's position, cited in the magazine “Orthodox Review” by a theologian and Konstantin Leontyev's follower Ivan Kristi are also analyzed. The reception of Solovyov's theocratic ideas and reaction to his ecclesiastical views in both the Catholic and Orthodox circles of Russian and Western society is shown. Especially it concerns the criticism of Solovyov’s ideas in the pages of the French magazines “L’Univers”, “L'Union Chrétienne”, “Revue d’Eglise greque-unie”, etc. The evolution of Solovyov's views on the problem of the union of Eastern and Western churches, the renewal of church communication between Orthodoxy and Catholicism, the main result of which was his fundamental but unfinished work “The History and Future of the Theocracy” (Zagreb, 1887) was demonstrated. A conclusion about the “superficiality” of the judgments of the majority of Vladimir Solovyov's ideological opponents, as well as later interpreters of his legacy, following the French Jesuit Michel d'Erbigny, who tried to present him as a “Russian Newman” who converted from Orthodoxy into the Catholic faith is drawn. It is shown that Solovyov’s projects of the “religion of the Holy Spirit” and the “Universal Church”, created on its basis, should be considered primarily in the context of his own philosophical quest, and not in connection with the confessional and ideological divergences of his time.